Point-of-Care Ultrasound to Evaluate the Acute Abdomen: A Case of Bowel Perforation After Unknown Single Magnet Ingestion. Issue 2 (10th February 2022) - Malik, Rabia; Leviter, Julie; Gross, Isabel; Saluja, Saurabh; Cowles, Robert A.; Riera, Antonio
Abstract : Supplemental digital content is available in the text. Abstract: We report the case of a 3-year-old boy who presented to the pediatric emergency department in undifferentiated shock with an acute abdomen. Point-of-care ultrasound revealed viscous perforation with a large amount of free fluid. Intraoperatively, a single magnet was discovered as the likely cause of bowel perforation and the resulting state of shock.